Atensi Kepala Sekolah terhadap Perpustakaan sebagai Pusat Sumber Belajar - Sri Hardianty (Program Studi Manajemen Pendidikan Islam, 2022)
The principal as a leader must be responsible for everything in the school. Starting from the problems of educators, students, the teaching and learning process, the quality of education in schools to the existing facilities and infrastructure in schools including libraries. The principal must give full attention to the school library so that the organization can provide maximum benefits to help achieve educational goals in schools. The urgency of the existence and empowerment of school libraries must be fully realized by the principal so that the library is not only a supporting unit in schools but can be a center of learning resources for all school residents. The principal's attention to the library can be done by always providing motivation, advice, guidance, appreciation, supervision and fulfillment of all library resource needs. The principal must seek a budget for the procurement of various library materials, infrastructure, human resources and programs or activities in the school library. The principal can also establish good coordination and cooperation with various parties such as school committees, teachers, parents, education staff, students, residents around the school and even the business world. To be able to achieve this, the attention given by the principal to the library must be based on a high and sustainable commitment and sense of responsibility.